Автоматизація процесу формування штатного розкладу в регіоні залізниці - Мартинов, І. Е.; Меркулов, В. С.; Бізюк, І. Г.; Петрова, Р. В. (УкрДУЗТ, 2018)
Automation of process of definition and optimization of numerical and qualitative structure of employees of cargo stations of the railroad is getting a particular importance in modern conditions of development of information technologies. Article is devoted to questions of the organization of a subsystem of formation of the staff list which is a component of the automated system of operational planning loading – unloading works in the region of the road and is operated in department of planning of transportations and the organization of cargo work of a commercial department of regional branch "Southern railroad". The functional structure of a subsystem, structure of a database, the user interface, the regulations of work and information security measure are considered. The appeal to a database happens if it is necessary to receive a selection by certain inquiries or to update the available information. Database fragments (sites, stations,...) are characterized by objects (reporting and help documents, telegrams,...), processes (saving of information, editing and formation of sheets,...) and users (staff of department of the organization of work of stations, relevant services of the railroad and cargo stations). The human-machine interface is based on a dialogue combination in the form of "menu" and possibility of the user in the course of work "to move" on the object by means of cursor arrows, a mouse or combinations of function keys. Discretionary approach to information security is applied, besides, check on an admissibility is carried out and in the course of work copies of operational data are periodically made. Ways of improvement of the described subsystem, namely addition with its simulars of situations, decision-making with use of expert estimation are offered. Operating experience of the offered software product has confirmed its efficiency.
Keywords: loading unloading; automation; database; site; station; rate; salary; interface